Caracterização biométrica, fisiológica e bioquímica de sementes de genótipos de feijão em função de doadores de óxido nítrico. - Carvajal, Nohora Astrid Velez (2020)
Beans (Phaseolus vulgaris L.) are among the food grade legumes, the most important species for human consumption because of their great nutritional value, as they are an important source of protein, vitamins and iron. Bean crop is one of the most sensitiv